TMAO and diabetes: from the gut feeling to the heart of the problem - Kinga Jaworska; Monika Kuś; Marcin Ufnal (Nutrition & Diabetes, 2025)
Abstract Elevated plasma levels of trimethylamine N-oxide (TMAO)—a compound derived from diet and the gut microbiome—have been widely studied for their association with diabetes risk and their potential role in disease pathophysiology and complications. However, clinical studies, both prospective and retrospective, have yielded conflicting results. For example, elevated levels of TMAO are frequently linked to an increased risk of cardiovascular and renal complications in individuals with diabetes. However, the robustness and independence of these associations differ across study populations and are influenced by the degree of adjustment for confounding risk factors. Considering insulin’s regulatory effect on FMO3 activity in liver cells, TMAO may serve as a marker of hepatic insulin resistance, which could partially explain its association with diabetes risk. The role of TMAO in diabetes pathology remains controversial; while some studies emphasize its detrimental impact on insulin sensitivity and the progression of diabetes-related complications, others suggest potential protective effects. Investigating the largely unexplored role of TMAO’s precursor, trimethylamine, may help elucidate these discrepancies. This review consolidates clinical and experimental findings to clarify TMAO’s complex mechanistic contributions to diabetes pathology.